Intelligent computer mathematics : International Conference, CICM 2015, Washington, DC, USA, July 13-17, 2015, Proceedings /: International Conference, CICM 2015, Washington, DC, USA, July 13-17, 2015, Proceedings. (2015) - Unknown
No abstract available